Selective Hydrogen Atom Abstraction through Induced Bond Polarization: Direct α‐Arylation of Alcohols through Photoredox, HAT, and Nickel Catalysis. (6th April 2018) - Twilton, Jack; Christensen, Melodie; DiRocco, Daniel A.; Ruck, Rebecca T.; Davies, Ian W.; MacMillan, David W. C.
Abstract: The combination of nickel metallaphotoredox catalysis, hydrogen atom transfer catalysis, and a Lewis acid activation mode, has led to the development of an arylation method for the selective functionalization of alcohol α‐hydroxy C−H bonds. This approach employs zinc‐mediated alcohol deprotonation to activate α‐hydroxy C−H bonds while simultaneously suppressing C−O bond formation by inhibiting the formation of nickel alkoxide species. The use of Zn‐based Lewis acids also deactivates other hydridic bonds such as α‐amino and α‐oxy C−H bonds. This approach facilitates rapid access to benzylic alcohols, an important motif in drug discovery. A 3‐step synthesis of the drug Prozac exemplifies the utility of this new method.